Model of Islamic Religion Education 435 Based on Islam Nusantara on College - Umi Zulfa (FITK UIN Walisongo, 2018)
This paper aims to provide an alternative model of Islamic Religion Education Based on Islam Nusantara on College, that make students able to emerge as wise leaders in the midst of Indonesian society and far from being exclusive. This research used qualitative approach with type of research library. The result sawn that Islamic Religion Education model of Islam Nusantara in college is built from 435 Islam Nusantara concept that is a model consisting of four (4) character, they are spirit of religious education process. Namely: ruuhuddin (religious spirit), nationalism, ruuhudta'addudiyah (spirit of diversity) and ruuhul insaniyyah (spirit of humanity), built on 3 main pillars: thought (fikrah), movement (harakah), real action (amaliyyah), and with 5 markers, namely islakhiyyah, tawazunniyah, tatawwuniyah, akhlaqiyah, and tasamuh.. Abstrak Tulisan ini bertujuan untuk memberikan model alternatif Pendidikan Agama Islam Berbasis Islam Nusantara di Perguruan Tinggi, yang membuat siswa mampu tampil sebagai pemimpin yang bijaksana di tengah masyarakat Indonesia dan jauh dari eksklusif. Penelitian ini menggunakan pendekatan kualitatif dengan jenis perpustakaan penelitian. Hasil penelitian menunjukkan bahwa model Pendidikan Agama Islam Islam Nusantara di perguruan tinggi dibangun dari 435 konsep Islam Nusantara yaitu model yang terdiri dari empat (4) karakter, yaitu semangat proses pendidikan agama. Yakni: ruuhuddin (semangat agama), nasionalisme, ruuhudta'addudiyah (spirit of diversity) dan ruuhul insaniyyah (semangat kemanusiaan), dibangun di atas 3 pilar utama: pemikiran (fikrah), gerakan (harakah), aksi nyata (amaliyyah), dan dengan 5 penanda, yaitu islakhiyyah, tawazunniyah, tatawwuniyah, akhlaqiyah, dan tasamuh.